2013
DOI: 10.1118/1.4807090
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of dose perturbations induced by external and internal accessories in ocular proton therapy and evaluation of their dosimetric impact

Abstract: The degree of disturbance by external beam shaping devices remains low in ocular proton therapy and can be reduced by bringing accessories closer to the eye. Tantalum fiducial markers must be located in such a way that dose perturbation is not projected on the tumor. The treatment of patients with intraocular endotamponades must be carefully managed. It is fundamental that radiation oncologists and medical physicists are informed about the presence of such substances prior to the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Substantial recent improvements in on-board imaging systems, patient positioning, and patient immobilization have led to increased use of radiopaque implanted fiducial markers in proton therapy to many disease sites, with the goal of improving target coverage and/or normal tissue sparing. However, recent studies revealed that some commonly used markers, even those less than 1 mm in size, can cause severe cold spots (Figure 7), compromising target coverage (Newhauser et al , 2007a; Newhauser et al , 2007c; Carnicer et al , 2013). The severity of the cold spots varies with fiducial size, material composition, and mass density.…”
Section: Proton Interaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial recent improvements in on-board imaging systems, patient positioning, and patient immobilization have led to increased use of radiopaque implanted fiducial markers in proton therapy to many disease sites, with the goal of improving target coverage and/or normal tissue sparing. However, recent studies revealed that some commonly used markers, even those less than 1 mm in size, can cause severe cold spots (Figure 7), compromising target coverage (Newhauser et al , 2007a; Newhauser et al , 2007c; Carnicer et al , 2013). The severity of the cold spots varies with fiducial size, material composition, and mass density.…”
Section: Proton Interaction Mechanismsmentioning
confidence: 99%
“…Several studies reported that implanted metallic fiducials can cause dose shadows that may compromise local tumor control for certain diseases, e.g. , prostate carcinoma and uveal melanoma (Newhauser et al , 2007a; Newhauser et al , 2007c; Giebeler et al , 2009; Cheung et al , 2010; Huang et al , 2011; Matsuura et al , 2012; Zhang et al , 2012; Carnicer et al , 2013). …”
Section: Proton Transport Calculationsmentioning
confidence: 99%
“…The density of the tantalum material is not taken into account in both EYEPLAN and EOPP TPS where only an average of eye density of 1.05 g.cm −3 is assumed, although this value may be adjusted and vary among the centers 13,63 . The degree of disturbance can be high as raised by Carnicer et al 64 who established an underdose shadow of up to 20% downstream of their location associated with an overdose on either side of the beam paths and a shift reduction of 1.1 mm of the intended range along the central axis of the beam. Newhauser et al 65 reported dose perturbations between 22% and 82%, when investigating various clip positions and orientations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we previously measured the dose received due to secondary neutrons in conditions of ocular PT as 2.5 mSv. [35][36][37] It is possible that we missed other confounding causes of cataracts. 38,39…”
Section: Discussionmentioning
confidence: 99%